1984
DOI: 10.1029/jd089id06p09589
|View full text |Cite
|
Sign up to set email alerts
|

A diabatic circulation experiment in a two‐dimensional photochemical model

Abstract: A two-dimensional photochemical model based on diabatic circulation has been used to simulate the behavior of N20, CFC13 (F-11), and CF2Cl• (F-12). The circulation is based on estimates of net heating from the ground to 60 kin. Eddy diffusion has been reduced with respect to other model studies with Kzz --2 x 103 cm • s-• everywhere above 100 mbar. Resulting tracer profiles show reasonable agreement with measured profiles in the tropics and fall off much more sharply with altitude than those produced by models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The differences between calculations and observations for these species are somewhat larger than those shown above for methane and nitrous oxide, particularly in the tropics. It has been noted [e.g., Gidel et al, 1983;Guthrie et al, 1984] that this may indicate that the photolysis rates for these chlorocarbons are underestimated in present chemical models.…”
Section: The Importance Of Methane In Chlorine Chemistry Was Discussementioning
confidence: 99%
See 2 more Smart Citations
“…The differences between calculations and observations for these species are somewhat larger than those shown above for methane and nitrous oxide, particularly in the tropics. It has been noted [e.g., Gidel et al, 1983;Guthrie et al, 1984] that this may indicate that the photolysis rates for these chlorocarbons are underestimated in present chemical models.…”
Section: The Importance Of Methane In Chlorine Chemistry Was Discussementioning
confidence: 99%
“…Woodman and Rastogi [1984] have derived similar small vertical diffusivities using radar techniques. Guthrie et al [1984] and M. K. W. Ko et al (unpublished manuscript, 1984) have shown that the distribution of N20 calculated in diabatic and isentropic circulation models using these eddy coefficients as crude parameterizations of mixing processes is in good agreement with observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lation models included high diffusion [Prabhakara, 1963;Pyle and Rogers, 1980a;Miller et al, 1981], adopting diffusion coefficients similar to those usually used in the Eulerian models [Reed and German, 1965;Luther, 1973]. More recent diabatic models [Ko et al, 1985;Solomon and Garcia, 1984;Guthrie et al, 1984] have successfully simulated the distributions of ground-released long-lived constituents, e.g., N20, CH,•, and CF2C12 using slow diffusion, Kyy • 1-3 x 10 9 cm 2 s -1 and K:: • 10 3 cm 2 s -1. These model estimates indicate that the transport of long-lived tracers with sources at the ground can be described by the diabatic circulation combined with relatively small eddy diffusion.…”
mentioning
confidence: 99%
“…The RMC is then obtained as in the diabatic case but with the differenced temperature tendency subtracted from the heating rate. The temperature and circulations are used to drive a limited-chemistry model [Guthrie et al, 1984] in which N20 is used as a tracer. The cases were each run for ten model years and achieved repeating annual cycles in the tracer distributions.…”
Section: The Present Experimentsmentioning
confidence: 99%